1999
DOI: 10.1046/j.1365-2036.1999.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for Helicobacter pylori infection

Abstract: Although in vitro data appeared promising, in vivo results were disappointing. Higher doses, longer duration of therapy, adjunctive acid suppression, or a combination could possibly yield better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Opekun et al administrated 250 mg or 1 g recombinant human LF to 12 subjects five times in a 24-h period and found no significant change in the UBT value. 21 Guttner et al administrated 5 g recombinant human LF per day for 5 or 14 days, and found neither conversion of the UBT from positive to negative nor consistent decrease of UBT values with a possible suppression of H. pylori. 22 In contrast to the inefficacy of recombinant human LF, oral administration of bLF (200 mg b.i.d) in combination with a 7-day triple eradication regime (rabeprazole, clarithromycin, and tinidazole) was successful to eradicate H. pylori in 100% of patients, whereas the triple therapy eradication regimen without bLF was only effective in 76.9%.…”
Section: Discussionmentioning
confidence: 97%
“…Opekun et al administrated 250 mg or 1 g recombinant human LF to 12 subjects five times in a 24-h period and found no significant change in the UBT value. 21 Guttner et al administrated 5 g recombinant human LF per day for 5 or 14 days, and found neither conversion of the UBT from positive to negative nor consistent decrease of UBT values with a possible suppression of H. pylori. 22 In contrast to the inefficacy of recombinant human LF, oral administration of bLF (200 mg b.i.d) in combination with a 7-day triple eradication regime (rabeprazole, clarithromycin, and tinidazole) was successful to eradicate H. pylori in 100% of patients, whereas the triple therapy eradication regimen without bLF was only effective in 76.9%.…”
Section: Discussionmentioning
confidence: 97%
“…Several in vivo and in vitro studies regarding a monotherapy of bLF against H. pylori infection showed equivocal results. A recent study that assessed the clinical safety and efficacy of a recombinant human lactoferrin (hLf) monotherapy for H. pylori infection in adult subjects did not show significant eradication; 33 however, the authors suggested that the lack of effect was due to the limited number of subjects, and that as an adjuvant to long-lasting therapy or with concomitant acid-suppressing therapy it might have been more effective. Nevertheless, it is controversial whether hLf is effective against H. pylori, particularly since it is known to be a growth-supporting iron transport protein for bacteria, whereas bLf is not.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo efficacy of these products are also questionable. Opekun et al [22]treated healthy volunteers with H. pylori infection either with hyperimmune bovine colostrum immunoglobulins or recombinant human lactoferrin. Although in vitro data appeared promising, none of the subjects had their H. pylori removed.…”
Section: Discussionmentioning
confidence: 99%